Globalization and subjects' ideas about the career: Reality, illusions, opportunities and limitations - Tolochek, Vladimir A. (Saratov State University, 2024)
The relevance of the research issue is due to the following: an increase in the length of a person’s working life creates a socially and personally significant ‘second reality’ that comprises the individual’s ideas about oneself, about the profession, success, etc. Purpose: to study the subject’s ideas about one’s career. Hypotheses: 1) The subject’s ideas about their career (as the evolution of professional and working life) act as regulators of the dynamics of the processes of one’s age-related professional evolution. 2) Social experience and personal characteristics act as ‘internal conditions’ that determine the subject’s ideas about their career. Methods (tools): J. Rotter’s Locus of Control Scale (Level of Subjective Control) (in the adaptation of E. F. Bazhin, S. A. Golykina, A. M. Etkind) was used to determine the role of personal characteristics in the formation of ideas; the methodology ‘Dynamics of Professional Career’) (by V. A. Tolochek) was used to solve the direct research tasks. Participants: nurses (n1 = 99), students of a humanitarian university (n2 = 61) and of a technical university (n3 = 90), private security guards (n4 = 62), university teachers (n5 = 37) (Moscow, Volgograd, Samara, Krasnodar). Results: people’s ideas about professional and working life, about the evolution of their qualities aff ect the dynamics of ‘objective’ processes; social experience does not act as a factor that determines the degree of infl uence of external eff ects on human perceptions (including the conditions of professional self-realization in Russia and abroad). The main conclusions. It is necessary to purposefully form constructive ideas of a person about the real conditions of realization in the profession. A broad approach to the issue of human resource management as a ‘reverse economy’ is required (a set of tasks to reduce social costs, optimize the cost of education, training, staff rotation, health restoration, etc.). As a way to coordinate the results of individual studies, it is proposed to use the ‘vector of scientifi c concepts’ - the allocation of a continuum of connections between diff erent concepts of several disciplinary areas. Practical signifi cance. The results of the research can be used to correct particular and strategic tasks of human resource management.